1995
DOI: 10.1038/ng1295-450
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the mucosal keratin K4 is associated with oral white sponge nevus

Abstract: White sponge nevus (WSN) is a benign autosomal dominant disorder which affects non-cornifying stratified squamous epithelia (MIM 193900) (ref. 1). Phenotypically it presents as white 'spongy' plaques (oral leukokeratoses), most commonly in the mouth but also reported in the esophagus and anogenital mucosa. Histologically, the plaques show evidence of hyperproliferation, acanthosis and tonofilament aggregation. These types of pathogenic changes are characteristic of many of the epidermal keratin disorders. Kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(70 citation statements)
references
References 19 publications
5
65
0
Order By: Relevance
“…Mouse models for epidermolytic hyperkeratosis that express truncated KI and KIO proteins have also been reported Bickenbach et al, 1996) (Chan et al, 1994;Rugg et al, 1994;lonkman et al, 1996) (Jonkman et al, 1996;Waseem et al, 1999) and K14 "knock-out" mice (Lloyd et al, 1995), keratin K15 was the "compensating" keratin partner and is up-regulated in basal cells of K14-ablated human epidermis and hair follicles. Clearly, however, although K15 (Richard et al, 1995;Rugg et al, 1995) (Table 1). In all cases published to date, the heterozygous mutations lie in the helix initiation peptide within the LA portion of the ox-helical rod domain.…”
Section: (B) Skin Disorders Associated With Keratin Mutationsmentioning
confidence: 97%
“…Mouse models for epidermolytic hyperkeratosis that express truncated KI and KIO proteins have also been reported Bickenbach et al, 1996) (Chan et al, 1994;Rugg et al, 1994;lonkman et al, 1996) (Jonkman et al, 1996;Waseem et al, 1999) and K14 "knock-out" mice (Lloyd et al, 1995), keratin K15 was the "compensating" keratin partner and is up-regulated in basal cells of K14-ablated human epidermis and hair follicles. Clearly, however, although K15 (Richard et al, 1995;Rugg et al, 1995) (Table 1). In all cases published to date, the heterozygous mutations lie in the helix initiation peptide within the LA portion of the ox-helical rod domain.…”
Section: (B) Skin Disorders Associated With Keratin Mutationsmentioning
confidence: 97%
“…These results suggest that K4 is required for the maintenance of internal epithelial cell integrity. It has recently been shown that the human disorder white sponge nevus (WSN, OMIM 193900) is the result of mutations of either K4 or K13 (14,15). Although there are some differences in the spectrum of phenotypic manifestations in WSN patients and mice lacking the K4 protein, the mice could serve as genetic models for this disorder and may help us understand the pathophysiology resulting from the absence of K4 and the role of K4 in squamous epithelial cell differentiation.…”
mentioning
confidence: 99%
“…Among the genes placed in the contig, ALK1 was shown to be responsible for hereditary hemorrhagic telangiectasia type 2 (Johnson et al 1996), AMHR2 for persistent Mullerian duct syndrome, type II (Imbeaud et al 1995), and keratin type II genes for various genetic diseases. These keratin-associated diseases include ichthyosis bullosa of Siemens (Rothnagel et al 1994), monilethrix (Healy et al 1995;Winter et al 1997), epidermolysis bullosa simplex (Lane et al 1992), epidermolytic hyperkeratosis (Letai et al 1993), Meesmann corneal dystrophy (Irvine et al 1997), pachyonychia congenita, Jadassohn-Lewandowsky type (Bowden et al 1995), palmoplantar keratoderma, Bothnia type (Lind et al 1994;Kelsell et al 1995), white sponge nevus (Rugg et al 1995). Among these disorders, the genes for all but one, palmoplantar keratoderma, Bothnia type, were identified.…”
Section: Characteristics Of the Sts Content Map For The Region Spannimentioning
confidence: 99%